Narrative measures in psychotherapy research: introducing the special section. - Gonçalves, Miguel M. (2017)
[Excerpt] The aim of this special section is to present a review of recent advances in the assessment of changes in client narratives. An emerging trend in the psychotherapy research field suggests that narrative-based meaning reconstruction is an important foundation for the articulation of a new, more adaptive view of self (Angus & Kagan, 2013) in psychotherapy. Additionally, a range of research-informed treatment models, including psychodynamic (Luborsky, 1998), humanistic (Angus, Watson, Elliott, Schneider, & Timulak, 2015) and systemic therapy approaches (Dallos & Vetere, 2009), emphasize that client changeinpsychotherapyisfacilitatedthroughpersonal story disclosure, emotional engagement and reflection for new meaning construction and self-narrative reorganization. In fact, recent research from Angus et al. (inpress)andGonçalvesetal.(thisissue),usingdifferent methods and clinical samples, have independently established that successful psychotherapy involves client self-narrative transformation processes evidenced in late phase therapy sessions. (...)